Development and multifunctional investigation of reduced graphene oxide decorated MgO hybrid nanocomposite - M. Mylarappa; S. Chandruvasan; K.N. Shravana Kumara; G. Krishnamurthy; A.S. Santhosh Kumar (Hybrid Advances)
The current work reports magnesium oxide (MgO) nanoparticles were synthesized by solution combustion route and prepared MgO was incorporated on reduced graphene oxide (rGO) using simple reflux method. Here, XRD (X-ray Diffraction), XPS (X-ray photoelectron spectroscopy), SEM (Scanning electron microscopy), EDAX (Energy dispersive X-ray analysis) and Raman spectra were employed to confirm the sample. The prepared rGO/MgO exhibited 83 % antioxidant activity with lower IC50 value 2609.23 mg/mL. The capacitance (Csp), diffusion coefficient (D) and sensing property were evaluated. From cyclic voltammetry analysis (CV), the capacitance values of rGO and rGO/MgO electrodes were found to be 91.26 and 173.05 F/g. The lesser value of reversibility (EO−ER=1.98×10−5) with greater proton diffusion coefficient (D=1.812×10−6) demonstrate enhanced electrochemical performance using 1 M KOH electrolyte. The selected malachite green dye was effectively degraded up to 93 % within 150 min by first-order kinetics. The prepared rGO/MgO electrode has been used for evaluating the sensing activity of ascorbic acid (BS-A), resorcinol (BS-R), and uric acid (BS–U). The findings obtained demonstrated a higher detecting oxidation potential.